2007
DOI: 10.1183/09031936.00125106
|View full text |Cite
|
Sign up to set email alerts
|

Diaphragm dysfunction in chronic obstructive pulmonary disease: a role for heparan sulphate?

Abstract: In the present study, phage display-derived antibodies were used to investigate the topology of glycosaminoglycan epitopes in the diaphragm of chronic obstructive pulmonary disease (COPD) and non-COPD patients. Furthermore, the potential physiological significance of changes in the occurrence of glycosaminoglycan epitopes in the diaphragm of COPD patients was studied by determining the overlap in epitope recognition of glycosaminoglycan antibodies and growth factors.Diaphragm cryosections from non-COPD (n55) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
1

Year Published

2009
2009
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 47 publications
0
12
0
1
Order By: Relevance
“…The largest exceptions to this are the work of Lewis et al (43), who showed reductions in in vitro specific force of Ͼ20%, and Huenks et al (32), who demonstrated reductions of ϳ14%. In human studies of isolated fibers from biopsy specimens, two groups, Levine et al (40) and Ottenheijm et al (64), have found significant reductions in specific force in individual costal diaphragm fibers (Table 2), an observation recently confirmed in another group of COPD patients by these authors (86 1, increase; 2, decrease; TLC, total lung capacity; FRC, functional residual capacity;…”
Section: Changes In Specific Forcementioning
confidence: 83%
See 2 more Smart Citations
“…The largest exceptions to this are the work of Lewis et al (43), who showed reductions in in vitro specific force of Ͼ20%, and Huenks et al (32), who demonstrated reductions of ϳ14%. In human studies of isolated fibers from biopsy specimens, two groups, Levine et al (40) and Ottenheijm et al (64), have found significant reductions in specific force in individual costal diaphragm fibers (Table 2), an observation recently confirmed in another group of COPD patients by these authors (86 1, increase; 2, decrease; TLC, total lung capacity; FRC, functional residual capacity;…”
Section: Changes In Specific Forcementioning
confidence: 83%
“…It has been proposed that the adaptations of the diaphragm in COPD demonstrate a kind of muscle dysfunction or impairment (62)(63)(64)84). This may be true, and findings such as loss of Ca 2ϩ sensitivity and atrophy certainly lead us in this direction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Összességében, saját vizsgálati eredményeink cáfolják azt, hogy az OM egy szívizom-specifi kus miozin-aktivátor lenne, mivel jellegzetes hatásai némileg kisebb hatékonysággal, de lassú típusú vázizomrostokban is kialakultak. A vázizomros-tok Ca 2+ -érzékenyítése révén a jövőben az OM-et (és annak potenciálisan kifejlesztendő származékait) a vá-zizomzat krónikus elgyengülésével járó kórképekben is kipróbálhatják majd, mint alternatív terápiás eszközt (30,31). Jelenleg nem áll rendelkezésre olyan in vitro vagy in vivo tanulmány, amelyben az OM-hatásait vizsgálták volna légzési elégtelenségben.…”
Section: Preklinikai Vizsgálati Eredmények Omecamtiv Mecarbillalunclassified
“…6 Loss of skeletal muscle mass in COPD leads to muscle weakness. 7 which impairs respiratory muscle function resulting in pulmonary hyperinflation, Barrel chest and geometry of chest wall is altered with hyperinflation leading to chronic reduction of the opposition zone of the diaphragm 9.10 .Hyperinflation change the diaphragm fiber arrangement and length which is an important determinant of force generating capacity 8 . Pulmonary hyperinflation can shorten diaphragm fiber sarcomere displacing it from its optimal length precipitating a decrease in the mechanical efficiency of the muscle 12 .…”
Section: Introductionmentioning
confidence: 99%